Exploratory Research: Introducing Consumer Stability as an Informing Customer Segmentation Feature - Lankfer, Jonathan (2020)
Static simplicity has encapsulated the academic and industry application of customer segmentation ever since its introduction to the wider consumer behaviour discussion in the 1950s. Evolving traditional analytical methods to address their coarseness, this research provides justification for the introduction of consumer stability to extend and conceivably displace lifetime and single-visit basket analysis which saturates the existing segmentation conversation. Principal component analysis is applied to demonstrate consumer stability’s importance, represented in this research by temporally lagged RFM measures within an FMCG scenario. A k-Means clustering model is implemented to extend this exploratory research, providing an example of how latent behaviours could provide an opportunity for marketers to enhance their output by evaluating temporal consumption pathways.